2005
DOI: 10.1002/marc.200500131
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured Thermosetting Systems from Epoxidized Styrene Butadiene Block Copolymers

Abstract: Summary: Nanostructured thermosetting materials were prepared by modification of an epoxy resin with 30 wt.‐% epoxidized polystyrene‐block‐polybutadiene copolymer (PS‐b‐PepB). The copolymer self‐assembles into a well‐defined hexagonal nanoordered structure, of around 30‐nm diameter, thus establishing its use as structure‐directing agent to generate nanostructured thermosetting materials. The study confirms pathways towards tailoring interactions between thermosetting matrices and immiscible block copolymers by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(83 citation statements)
references
References 22 publications
4
73
0
Order By: Relevance
“…Diblock copolymers are able to form well-defined ordered and disordered nanostructures in thermosetting epoxy resins [1][2][3][4][5][6][7][8][9][10][11][12] based on their self-assembly capability. Nanostructured thermoset epoxy resin blends can be selforganized by addition of amphiphilic block copolymers that consist of a thermoset-miscible and thermosetimmiscible block.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diblock copolymers are able to form well-defined ordered and disordered nanostructures in thermosetting epoxy resins [1][2][3][4][5][6][7][8][9][10][11][12] based on their self-assembly capability. Nanostructured thermoset epoxy resin blends can be selforganized by addition of amphiphilic block copolymers that consist of a thermoset-miscible and thermosetimmiscible block.…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26] Whereas several studies have shown a new family of polymer-dispersed LCs, [27][28][29][30] where the LC is dispersed in a thermoplastic/thermoset matrix, to the best of our knowledge, the possibility of using block copolymers as modifiers in thermoset systems and their ability to act as thermally reversible nanostructured thermosetting materials have not been reported yet. Taking into account the work done by Hoppe et al [27,28] and our previous papers, [10][11][12][29][30][31][32][33] the main aim of the present contribution is to investigate the possibility of obtaining novel meso/nanostructured thermosetting materials, which can be thermally reversible based on a thermosetting system modified with a block copolymer and a nematic lowmolecular-weight LC. Bisphenol A-type epoxy resin, modified with an amphiphilic block copolymer based on polystyrene and poly(ethylene oxide) (PSEO) and a low-molecular-weight nematic LC, 4 0 -(hexyl)-4-biphenylcarbonitrile (HBC), has been cured with a stoichiometric amount of an aromatic amine hardener, m-xylylenediamine (MXDA).…”
Section: Introductionmentioning
confidence: 99%
“…2e-f) shows the presence of PB units in both the epoxy-rich phase and near to the PS cylinders. The self-assembly for SepB61-modified system has been recently reported [30] as PS cylinders, with average radius of 11-13 nm, arranged in an epoxy-rich phase containing both epoxidized and nonepoxidized PB segments (denoted by the presence of dark domains in the epoxy-rich phase), which seems to indicate at least some partial miscibility of the PepB block with the cured-epoxy matrix as a consequence of the non-epoxidized segments of PepB block. Some differences can be observed with respect to the other epoxidation degrees.…”
Section: Block Copolymers As Templates For Nanostructuring Thermosettmentioning
confidence: 98%
“…The ability of block copolymers to phase separate has found many useful applications. For instance, combining a high-modulus block with an elastomeric block will result in a strong but tough polymer [61][62][63][64][65]. Applications that require precise structural control such as electronics, membranes [66], or nanoparticle templating [67] utilize block copolymers.…”
Section: Block Copolymersmentioning
confidence: 98%